PROFIL KOMPETENSI PENGELOLAAN WIRAUSAHA MAHASISWA PROGRAM STUDI PENDIDIKAN EKONOMI - Dewi Koryati; Yuliana FH; Firmansyah Firmansyah (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2023)
Fostering an entrepreneurial spirit among students can be started by encouraging interest and entrepreneurial intentions among students The research objective was to identify the profiles of 39 student entrepreneurs based on 3 variables: 1) Business Planning; 2) Creativity and Business Innovation; 3) Business Management. Data collection through questionnaires and structured interviews. Test external validity using product moment and reliability test with test alpha. Questionnaire data were analyzed using the percentage formula and classified in the entrepreneurial profile category table (basic, medium, advanced). Interviews with 10 respondents were randomly selected based on the score category representatives. The research result of Economic Education Student Entrepreneurs showed their ability to run a business by following their interests and skills. They are mostly classified as profiles of part-time entrepreneurs and the rest are family-owned entrepreneurs. Aspects of business planning in the category advance, aspects of creativity and innovation in the student entrepreneurship category advance, and business management aspects in the medium category.